Flow-field analysis and performance assessment of rotating detonation engines under different number of discrete inlet nozzles - (:unkn) unknown (Elsevier BV, 2024)
This study explores in depth rotating detonation engines (RDEs) fueled by premixed stoichiometric hydrogen/air mixtures through two-dimensional numerical simulations including a detailed chemical kinetic mechanism. To model the spatial reactant non-unifo...
Keywords: Motores de detonación rotativa; Dinámica de fluidos